Center Stage: Performing a Needs Assessment of Campus Research Centers and Institutes. Issue 4 (19th May 2017) - Malone, Andrea; Martin, Lisa; Peters (Pi), Christie; Turner, Cherie; Vaughn, Porcia
ABSTRACT: Outreach to research centers and institutes is often overlooked in academic libraries. This article discusses a needs assessment conducted by the Liaison Services Department at the University of Houston Libraries that reviewed library services to centers and institutes at the University of Houston's main campus. The assessment was conducted for two purposes: to build collaborations with centers and to determine how the libraries might create new services and/or market existing services to meet the centers and institutes' growing research needs.